2009
DOI: 10.4049/jimmunol.0901760
|View full text |Cite
|
Sign up to set email alerts
|

γδ T Cell Immune Manipulation during Chronic Phase of Simian HIV Infection Confers Immunological Benefits

Abstract: Vγ2Vδ2 T cells, a major human γδ T cell subset, recognize the phosphoantigen (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP) produced by mycobacteria and some opportunistic pathogens, and they contribute to innate/adaptive/homeostatic and anticancer immunity. As initial efforts to explore Vγ2Vδ2 T cell-based therapeutics against HIV/AIDS-associated bacterial/protozoal infections and neoplasms, we investigated whether a well-defined HMBPP/IL-2 therapeutic regimen could overcome HIV-mediated immune suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…It was previously reported that HMBPP and IL-2 treatment during simian-HIV infection in vivo was associated with the increased production of IFN-g, TNF-a, IL-4, and IL-10 (18,34). In a healthy ex vivo context, we confirm an increased production of these cytokines after Vd2 cell expansion in response to HMBPP and further demonstrate the production of IL-6, IL-9, IL-15, and IL-17.…”
Section: Cd25supporting
confidence: 81%
“…It was previously reported that HMBPP and IL-2 treatment during simian-HIV infection in vivo was associated with the increased production of IFN-g, TNF-a, IL-4, and IL-10 (18,34). In a healthy ex vivo context, we confirm an increased production of these cytokines after Vd2 cell expansion in response to HMBPP and further demonstrate the production of IL-6, IL-9, IL-15, and IL-17.…”
Section: Cd25supporting
confidence: 81%
“…on May 10, 2018. by guest www.bloodjournal.org From pathologic translocation of microflora in the lamina propria and mesenteric lymph nodes after the massive depletion of mucosal CD4 ϩ T cells in acute and highly viremic stages of HIV-1 infection. 24 Importantly, and in line with what was recently demonstrated for V␥9V␦2 T cells in SIV-infected primates, 25 the establishment of novel protocols either inducing NKp30 expression on expanded V␦1 T cells in vivo or adoptively transferring in vitro differentiated NKp30 ϩ V␦1 T cells may be of great therapeutic value in the cure of HIV/AIDS.…”
Section: Nkp30-induced Production Of Cc-chemokines Suppresses Hiv-1 Rmentioning
confidence: 63%
“…[16][17][18][19] However, while the biological consequences of these perturbations remain unclear, therapeutic interventions aimed at expanding the V␦2 T-cell subset have resulted in enhanced neutralizing antibody titers in chronically SHIV-infected RMs. 20 The mechanism leading to enhanced V␦2 T cell cytokine production and elevated neutralizing antibody titers in this study was largely unknown.A better understanding of the mechanisms that underlie alterations in ␥␦ T-cell subsets is crucial for future therapeutic interventions aimed at modulating ␥␦ T cells. Chronic immune activation is closely associated with disease progression in HIV/SIV infection, and microbial translocation is well described as one cause of immune activation.…”
mentioning
confidence: 77%